KEEFEKTIFAN TEKNIK STORY TELLING DALAM PEMBELAJARAN SASTRA - Rukayah Rukayah; Aziz Thaba (JURNAL KONFIKS, 2017)
This study aims to: (1) describe the results of literary learning without using storytelling techniques, (2) to describe the results of literary learning using storytelling techniques, and (3) to determine the effectiveness of the storytelling model in literary learning. The results of the assessment show that (1) learning without using storytelling technique in literary learning does not reach completeness, (2) the learning of literature by applying storytelling technique has reached completeness, and (3) the effectiveness of storytelling technique of VIII students of SMP Negeri 2 Sungguminasa. This proves that using storytelling technique can improve student's learning in literature learning which is seen from the average value of control class, that is 75.3, while the experimental class gets the average value, that is 85.9. In addition, the observation data of each meeting indicates a change in student attitudes towards a more positive, both in terms of learning attitudes and activities. From the results of the analysis can be concluded that the application of effective storytelling techniques used in learning literature.